Problematika Kehidupan Muslim Minoritas di Asia Tenggara (Muslim Melayu Pattani, Muslim Moro, dan Muslim Rohingya) - Rafika Dewi Septia; Yenni Pusvita Dewi; Rizki Febriansyah; Ismail Ismail; Mindani Mindani (Yayasan Darusssalam Bengkulu, 2024)
Unlike the case with non-Muslim minorities who can live comfortably in a country with a Muslim population as the majority, the three Muslim entities mentioned above live in many conflicts with the government in the country they live in. The purpose of this study is to explore the problems and problems of Muslim life as a minority in several regions in Southeast Asia, namely Thailand, the Philippines and Myanmar. The result of this study is that from the three ethnic Muslim minorities, the case is almost the same, namely experiencing rejection, torture murder and discrimination from the Government where they live, but so far discrimination against Rohingya Muslims is the worst discrimination, this is in line with what Human Rights says, Rohingya Muslims are the most oppressed Muslim Minority ethnicity.